Development and application of a multiplex PCR system for drowning diagnosis. Issue 11 (20th March 2021) - Xiao, Cheng; Xu, Quyi; Li, Huan; Zhu, Xiaolin; Yu, Zhonghao; Zhao, Jian; Li, Yue; Liu, Hong; Shi, He; Liu, Chao
Abstract: In recent years, the DNA detection of drowning‐related diatoms, cyanobacteria, and aeromonas has gradually attracted interest from forensic scientists. In this study, we described the validation and application of a novel multiplex PCR system. This system integrated 12 fluorescently labelled primers designed to amplify specific genes of diatoms, cyanobacteria, and aeromonas. The specificity studies demonstrated that this multiplex PCR system could detect nine species of diatom, seven species of cyanobacteria, and five species of aeromonas, all of which were drowning‐related and widely distributed in various water circumstance of southern China. The sensitivity studies indicated that the limit concentration of template DNA was 0.0125 ng. Besides, this multiplex PCR system had good performance in sizing precision and stability, but it is not suitable for degraded DNA samples. The application into forensic casework showed that all the tissue samples from ten nondrowning cases showed negative results, and the positive rates of lung, liver, kidney, and water samples from 30 drowning bodies were 100, 86.7, 90, and 100%, respectively. Combined with results of diatom tests of MD‐VF‐Auto SEM method, this multiplex PCR system could help rule out nondrowning bodies and provide extra evidences to support drowning diagnosis, especially for those cases with few diatoms observed. It is expected that this multiplex PCR system has great potential for forensic drowning diagnosis.